Unity in Diversity: Coinfluence of Basic Mythological and Philosophical Systems of India - O. G. Ulltsiferov (Vestnik MGIMO-Universiteta)
The article examines one of the main questions of intercommunications between main religious and cultural systems in India: Hinduism, Buddhism, Islam and Christianity. The article, using detailed factual material, focuses the similarities and differences between those systems, results in the basic data regarding ontology, cosmology, ethics and sociology of those systems. The article shows the interaction and mutual enrichment of so different systems.